Māori resource management innovations - Bargh, Maria (Routledge Handbook of Critical Indigenous Studies, 2020)
The historical context of colonial legacies and capitalist policies are shaping responses to climate change but so too are non-capitalist and alternative-capitalist practices. Indigenous peoples’ world-views are commonly argued to align with non-capitalist approaches and often said to be the answer to climate change. However, Indigenous peoples are never only ‘ecological natives’ ‘living at one with nature’ but have multiple roles and identities in the political economy. Indigenous world-views could be used in ways to support capitalist practices and policies (which many argue have caused climate change) or to support alternative-capitalist practices (which others argue promote harmonious relationships between humans and the planet).
Keywords: capitalism; climate change; environment

A Tika Transition - Bargh, Maria (A Careful Revolution Towards a Low-emissions Future, 2019)
Climate crisis is upon us. By choice or necessity, New Zealand will transition to a low-emissions future. But can this revolution be careful? Can it be attentive to the disruptions it inevitably creates? Or will carefulness simply delay and dilute the changes that future people require of us? This timely collection brings together eleven authors to explore the politics and practicalities of the low-emissions transition, touching on issues of justice, tikanga, trade-offs, finance, futurism, adaptation, and more.
Keywords: climate change; economic aspects; environmental management